2010
DOI: 10.1016/j.bcp.2010.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combretastatin A4 analogous chalcone and its Pt-complex on cancer cells: A comparative study of uptake, cell cycle and damage to cellular compartments

Abstract: Effects of a combretastatin A4 analogous chalcone and its Pt-complex on cancer cells: a comparative study of uptake, cell cycle and damage to cellular compartments. Biochemical Pharmacology, Elsevier, 2010, 80 (10) Please cite this article as: Zoldakova M, Kornyei Z, Brown A, Biersack B, Madarász E, Schobert R, Effects of a combretastatin A4 analogous chalcone and its Pt-complex on cancer cells: a comparative study of uptake, cell cycle and damage to cellular compartments, Biochemical Pharmacology (2008Pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…Also, several studies revealed that some chalcones and flavonoids can trigger apoptosis by modulating signaling pathways such as phosphatidylinositol-3-kinase/Akt and MAPK (mitogen-activated protein kinase), affecting many cellular functions such as gene regulation (Zoldakova et al 2010). Other studies report that chalcones actively interfere in ROS levels in T98G and U87MG glioma cell lines, causing changes in mitochondrial potential and MAPKs phosphorylation (Wiseman & Halliwell 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Also, several studies revealed that some chalcones and flavonoids can trigger apoptosis by modulating signaling pathways such as phosphatidylinositol-3-kinase/Akt and MAPK (mitogen-activated protein kinase), affecting many cellular functions such as gene regulation (Zoldakova et al 2010). Other studies report that chalcones actively interfere in ROS levels in T98G and U87MG glioma cell lines, causing changes in mitochondrial potential and MAPKs phosphorylation (Wiseman & Halliwell 1996).…”
Section: Discussionmentioning
confidence: 97%
“…10,11 Now we could show them by light microscopy to also cause inter-nucleosomal DNA cleavage in 518A2 melanoma cells (Fig. 10,11 Now we could show them by light microscopy to also cause inter-nucleosomal DNA cleavage in 518A2 melanoma cells (Fig.…”
Section: Biological Evaluationmentioning
confidence: 95%
“…4,5 Further chalcones were reported with high anticancer activities originating from other modes of action such as the inhibition of resistance-relevant ABC-transporters. 11 Herein we report on a close analogue of 3 bearing a different stationary 1-carboxyethane-2,3-diamine ligand and how it differs from 2 and 3 in terms of cytotoxicity, DNA binding and robustness against deactivation by glutathione. 9 Our group presented a dichlorido-Pt(II)-(6-aminomethyl)nicotinate 3 of chalcone 2 that combines DNA and tubulin binding properties and which inhibits the growth of certain cisplatin-resistant tumour cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…These candidates were further tested in vivo and found to be nontoxic in animal models. Zoldakova et al [29] also reported on combretastatin-like chalcones and identified a candidate demonstrating marked microtubule disruption and cell-cycle arrest in melanoma 512A cells and neural cells. Presumably a similar tubulin-binding mechanism is also at play.…”
Section: Chalcones Target Tubulin Polymerizationmentioning
confidence: 99%